(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Recently, many devices have been installed at the outer sea for different purposes, such as measuring the ocean environment and detecting enemies. Such devices installed at the outer sea require a consistent energy source to provide sufficient energy, and this energy source should be clean to reduce carbon emissions. The wave energy satisfies these requirements and is getting attention. A point absorber is a typical wave energy converter used for these devices. This study includes a numerical analysis to evaluate the motion responses of a two-body point absorber. The point absorber model consists of a floater, which mainly converts the wave energy, and a spar, which guides the floater to move in the heave direction. Target wave conditions are chosen based on the sea state of Korea, including both ideal regular wave conditions and irregular wave conditions. The numerical analysis is done using a frequency-domain boundary-element-method program, WAMIT. The numerical simulation results are validated with the model test results. The motion responses for single-body cases are compared with those of a two-body integrated system. Also, the generated power is estimated by assuming the damping of the power take-off system. Future studies will focus on the integrated performance of two-body point absorbers, including the actual second and third-wave energy conversion systems.